2020
DOI: 10.3390/electronics9101613
|View full text |Cite
|
Sign up to set email alerts
|

IoT System for School Dropout Prediction Using Machine Learning Techniques Based on Socioeconomic Data

Abstract: School dropout permeates various teaching modalities and has generated social, economic, political, and academic damage to those involved in the educational process. Evasion data in higher education courses show the pessimistic scenario of fragility that configures education, mainly in underdeveloped countries. In this context, this paper presents an Internet of Things (IoT) framework for predicting dropout using machine learning methods such as Decision Tree, Logistic Regression, Support Vector Machine, K-nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
17
0
4
Order By: Relevance
“…Notably, the authors propose the automation of the prediction process that contributes to the accurate prediction of student learning outcomes without analyzing the bulk of data. The result of this research indicated Decision Tree is a viable option to predict university graduation outcomes with 99.34% accuracy, 99.34%F1 score, 100%recall, and 98.69%precision [8]. According to [8], it outperformed others like Naïve Bayes, Logistic Regression, Support Vector Machines, K-Nearest Neighbors, and Multi-Layer Perceptron.…”
Section: Literature Reviewmentioning
confidence: 89%
See 3 more Smart Citations
“…Notably, the authors propose the automation of the prediction process that contributes to the accurate prediction of student learning outcomes without analyzing the bulk of data. The result of this research indicated Decision Tree is a viable option to predict university graduation outcomes with 99.34% accuracy, 99.34%F1 score, 100%recall, and 98.69%precision [8]. According to [8], it outperformed others like Naïve Bayes, Logistic Regression, Support Vector Machines, K-Nearest Neighbors, and Multi-Layer Perceptron.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The result of this research indicated Decision Tree is a viable option to predict university graduation outcomes with 99.34% accuracy, 99.34%F1 score, 100%recall, and 98.69%precision [8]. According to [8], it outperformed others like Naïve Bayes, Logistic Regression, Support Vector Machines, K-Nearest Neighbors, and Multi-Layer Perceptron. Other studies like [9], [14], [15], [16] and [17] have achieved better accuracies with other algorithms, such as educational data mining (EDM), Neural Network, Support Vector Machines, and Machine Learning, that would be applicable in predicting university dropout.…”
Section: Literature Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…The paper presents a data mining case study to create a model that would help learning institutions identify the key factors of Postgraduate degree students' dropout and delay at university. A decision tree algorithm is a feasible alternative to accomplish this task since it has achieved the best outcomes, reaching 100% recall, 99.34% accuracy, and 98.69 precision [1]. Other algorithms, such as Neural Network and Logistic Regression, provide better means of classifying data, although they are outperformed continuously by decision tree [2].…”
Section: Introductionmentioning
confidence: 99%